Imaging for Plasma Cell Dyscrasias: What, When, and How? - Guha, Amrita; Vijan, Antariksh; Agarwal, Ujjwal; Goda, Jayant Sastri; Mahajan, Abhishek; Shetty, Nitin; Khattry, Navin (Frontiers in Oncology, 2022)
Imaging plays a vital role in diagnosis, response assessment and follow-up of patients with plasma cell bone disease. The radiologic diagnostic paradigm has thus far evolved with developing technology and availability of better imaging platforms, however the skewed availability of these imaging modalities in developed vis-a-vis the developing countries along with the lack of uniformity in reporting has led to a consensus on the imaging criteria for diagnosing and response assessment in plasma cell dyscrasia. Therefore, it is imperative for not only the radiologists but also the treating oncologist to be aware of the criteria and appropriate imaging modality to be used in accordance to the clinical question. The review will allow the treating oncologist to answer the following questions on the diagnostic, prognostic and predictive abilities of various imaging modalities for plasma cell dyscrasia.: • What lesions can look like MM but are not? • Does the patient have MM? To diagnose MM in a high risk SMM patient with clinical suspicion-which modality to use and Why? • Is the patient responding to therapy on follow up imaging once treatment is initiated? • To interpret commonly seen complications post therapy -when is it disease and when is expected sequel to treatment. Fractures, Red marrow reconversion?. • When to flag a patient for further workup when interpreting MRI spine done for backpain in the elderly? To differentiate between commonly seen osteoporosis related degenerative spine vs marrow infiltrative disorder.